IN-VITRO ANTIOXIDANT ACTIVITY AND GC/MS STUDIES ON THE LEAVES OF MENTHA PIPERITA (LAMIACEAE) FROM MOROCCO (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
The present study was to evaluate the in vitro antioxidant activity and chemical composition of essential oil of Mentha piperita from Morocco. Mentha species from the Lamiaceae family are widely distributed in Morocco and commonly used as herbal tea, flavoring agent and medicinal plant. In this stud y, the essential oils of Mentha piperita collected in the region of Meknes (Morocco) were obtained by hydro-distillation of the leaves and analysed by gas chromatography equipped with flame ionisation detector (GC-FID) and gas chromatography coupled to mass spectrometry system (GC/MS) for their chemical composition. The antioxidant activity of essential oils against DPPH radical was determined in vitro by treated with different concentrations of essential oil and vitamin C as standard antioxidant compound. The percentages of DPPH inhibition and IC50 were recorded. Thirty compounds were identified in leaves oil representing 58.61% of the total oil composition. The yield of essential oil of Mentha piperita was 1.02% and the major compound in the leaves was: Menthone (29.01%) followed by menthol (5.58%), menthyl acetate (3.34%), menthofuran (3.01%), 1,8-cineole (2.40%), isomenthone (2.12%), limonene (2.10%), α-pinene (1.56%), germacrene-D (1.50%), β-pinene (1.25%), sabinene (1.13%) and pulegone (1.12%). The radical scavenging activity (% inhibition) of the essential oil from Mentha piperita was the highest (81.09± 1.21%) at the concentration of 150µg/ml and the IC50 values of these plant extracts were 53.67µg/ml.